Criptorquidia e exposição in utero ao di(n-butil)-ftalato e à acrilamida: avaliação morfológica do dano testicular - Souza, Nathália Pereira de [UNESP] (2015)
The testicular dysgenesis syndrome (TDS) encompasses conditions such reduced semen quality, hypospadia, cryptorchidism and testicular germ cell tumors (TGCT), which may occur isolated or in association. The influence of environmental factors on TDS occurrence has become increasingly evident, special attention being paid to exogenous chemicals such phthalates and acrylamide (AA), well known testicular toxicants. Experimentally induced cryptorchidism can be an useful experimental tool to understand TDS pathogenesis. It has been reported that the testicular microenvironment is critically modified when rodents are experimentally exposed to dibutyl-phthalate (DBP), to AA or to cryptorchidism. However, the combined influence of cryptorchidism and testicular toxicants has not been explored. This study aimed to evaluate the morphological changes and the immunoexpression of the transcription factor binding octamer ¾ (OCT¾) and the luteinizing hormone receptor (LHR) in the testes of rats submitted to a model of testicular damage that associated chemicals (DBP or AA) and surgical (cryptorchidism/orchidopexy) treatments. In utero and postnatal DBP or AA exposures associated with surgically-established cryptorchidism induced disruption of spermatogenesis and increased the expression of OCT¾ in germ cells. Immunoreactivity of LHR was qualitatively decreased in the cryptorchid group also exposed to DBP. Exposures to DBP or AA did not alter the anogenital distance. All experimental groups showed decreased in the epididymis weights. Relative ventral prostate weights was decreased in cryptorchid animals and relative liver weights was decreased in DBP-exposed animals. The orchidopexy performed 3 weeks after cryptorchidism was effective to reestablish fairly the testes structure and reproductive organs weights. Our results indicate that the model used, which associated chemical exposures to surgical interventions, may be useful to understand TDS ...